Pesantren vis a vis Global Challenges, Strengthening Vision of Pesantren Education - Moh Inami (Murabby: Jurnal Pendidikan Islam, 2021)
Education in this Muslim-majority country has large and important role in the whole Indonesia human development. The existence of education is the pillars of science and knowledge building that is capable of clicking deliver the people to development and progress.The development and progress are born and appear in the middle of people's life becomes a necessity. Occurrences that simply can’t be expected when people underestimate and ignore education.As, Islamic education is a priority. Through Islamic education that a good life is expected. With the Islamic education, progressed society can be realized. The good life and progressed society are characteristic and noble ideals.The presence of Pesantren as a representation of Islamic educational institutions can’t be circumvented. Pesantren, dictionary of Indonesianness, an Islamic institution which indigenous.However, as time went on, a tough challenge was in sight. Globalization has brought tremendous impact to the joints of human life in the hemisphere. Can Pesantren maintain its existence? What are there global challenges to watch out? How to strengthen the Pesantren educational vision in the face of global challenges?